VIBRATIONAL CASE STUDY FOR THE MOLD OSCILLATOR WITH HYDRAULIC SERVO SYSTEM - YONGHUI PARK; LEE CHANGWOO; KIM DONGWOOK (Journal of Engineering Studies and Research)
We have conducted sensitivity analysis to investigate the two-hydraulic-servo system for the mold oscillator. By modelling mathematical models for operating fluid flow to control a hydraulic cylinder, we changed design parameters and environment conditions including friction, additional spring stiffness and fluid leakage. From the one-hydraulic servo system to the two-hydraulic cylinder, modal analysis was conducted to figure out dynamic characteristics of the real system. Especially, we categorized important natural mode shape. When the system was excited into the natural frequency, the 1st mechanical natural frequency could cause a pressure gain by reducing internal pressure of a hydraulic cylinder, but other natural frequencies were critically dangerous by generating imbalance, over-vibration and distortion. By comparing the results to the experimental data, we could find a dramatic pressure drop near 3 Hz oscillation when the system has the 1st mechanical natural frequency 2.499 Hz. Also, the system has the imbalance near 6 Hz oscillation when the system has 2nd mechanical natural frequency 5.446 Hz. Based on these fact, we have suggested some tips to oscillate a mold efficiently and safely.